2010
DOI: 10.12681/mms.78
|View full text |Cite
|
Sign up to set email alerts
|

Golden Horn Estuary: Description of the ecosystem and an attempt to assess its ecological quality status using various classification metrics

Abstract: In this paper, we describe the pelagic and benthic ecosystem of the Golden Horn  estuary opening into the Marmara Sea. To improve the water quality of the estuary, which had long been subject to severe anthropogenic pollution (industrial, chemical, shipping),  industrial facilities were moved from the estuary in the 1980s, followed by a rehabilitation plan in the 1990s. Our results, based on chemical parameters and phytoplankton showed some signs of improvement of water conditions in the upper layer. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…However, the CF of mullet from adjacent estuaries of the Black Sea (Bilgin et al ., 2006) mostly ranged between 0.7 and 1.1 (lowest ~0.3), while the majority of CF values ranged between 1.0 and 1.5 (lowest 0.68) in our study. The higher CF found in the Sea of Marmara may be related to the high nutrient capacity of the Golden Horn estuary (Albayrak et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the CF of mullet from adjacent estuaries of the Black Sea (Bilgin et al ., 2006) mostly ranged between 0.7 and 1.1 (lowest ~0.3), while the majority of CF values ranged between 1.0 and 1.5 (lowest 0.68) in our study. The higher CF found in the Sea of Marmara may be related to the high nutrient capacity of the Golden Horn estuary (Albayrak et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Two streams, Alibeyköy and Kağıthane, provide the main freshwater inflow (Figure 1). However, the inflow from these tributaries has been severely reduced due to the construction of several dams in the watershed (Kınacı et al ., 2004; Albayrak et al ., 2010).
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…However, BENTIX was more sensitive than AMBI to the organic matter content increase in the sediment and related changes in macrobenthic assemblage, and BEN-TIX was better than AMBI in discriminating the stations. BOPA classified a station in the extremely polluted Golden Horn estuary (Albayrak et al, 2010) as "High" because the station did not include any polychaete species, but more than 80% of the individuals belonged to tolerant Oligochaeta. On the other hand, BO2A classified the same station as "Poor".…”
Section: Discussionmentioning
confidence: 99%
“…Albayrak et al (2006) studied the EQS of northern Marmara Sea and indicated that AMBI failed to detect the spatial differentiation of EQS, but BENTIX succeeded in 70% of the cases in producing an ecologically relevant classification reflecting the environmental pressures. Albayrak et al (2010) studied the ecological quality status of the extremely polluted Golden Horn Estuary in İstanbul and stated both AMBI and BENTIX showed 80% agreement with final assessment whereas BOPA showed 20% and BO2A showed 40% agreement. In this study, AMBI and especially BENTIX were more successful in identifying the ecological quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation